Green Supply Chain Performance Measurement using Green SCOR Model in Agriculture Industry: A Case Study - Arjuna, Arjuna; Santoso, Santoso; Heryanto, Rainisa Maini (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2022)
The agriculture industry has proliferated in the last decades, increasing the environmental footprint. Several development concepts include integrating the ecological aspect into the supply chain to reduce environmental degradation. In implementing the idea, companies in the agriculture industry need to evaluate their performance in the environmental area. This measurement uses the Green Supply Chain Operations Reference (GSCOR) Model that provides its entire supply chain aspect. This study demonstrates that the enable parameter criterion, which shows the magnitude of employee management toward environmental requirements, significantly impacts supply chain performance. Other criteria are also critical, such as a plan that considers every entity's usage and a source that considers the supply of the entities. The performance measurement produces a 6.357 value in the yellow color category with an average condition in the company. It produces three key performance indicators (KPI), such as water usage, percentage hazardous materials in inventory, and percentage hazardous waste, with a red classification that should be improved.